Journal of Analytical Science and Technology - Cheong, Chaejoon
The Journal of Analytical Science and Technology (JAST) is a fully open access peer-reviewed scientific journal published under the brand SpringerOpen. JAST was launched by Korea Basic Science Institute in 2010. JAST publishes original research and review articles on all aspects of analytical principles, techniques, methods, procedures, and equipment. JAST’s vision is to be an internationally influential and widely read analytical science journal. Our mission is to inform and stimulate researchers to make significant professional achievements in science. We aim to provide scientists, researchers, and students worldwide with unlimited access to the latest advances of the analytical sciences.